A Natural Anthraquinone Plants with Multi- Pharmacological Activities (Texas Journal of Medical Science, 2022)
Anthraquinone derivatives are naturally occurring compound, extracted from medicinal plants (Cascara, Frangula, Aloe, Rhubarb, Senna, and Rumex) of consolidated use in folk medicines as well as in modern medical practice, which have attracted attention of scientists, and still represent remarkable remedies in the treatment of many diseases, especially acute and chronic constipation.